2015
DOI: 10.1002/oby.21267
|View full text |Cite
|
Sign up to set email alerts
|

Late prematurity and adiposity in adolescents: Evidence from “Children of 1997” birth cohort

Abstract: Late prematurity was associated with higher BMI and waist ratios in adolescence, but only the association with BMI was mediated by infant weight gain, suggesting vulnerability to metabolic risk in late premature births may arise through multiple pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 43 publications
(58 reference statements)
4
16
1
Order By: Relevance
“…Specifically, we identified increased body mass, increased RV mass, and a decreased RV ejection fraction in rats 1 year after postnatal Hx, consistent with clinical studies of adults born prematurely (10,31). Our model was also characterized by chronic RV pressure overload due to hypertensive pulmonary vascular disease, as well as intrinsic RV dysfunction noted by the inability to maintain contractility in the setting of increased afterload.…”
Section: Discussionsupporting
confidence: 83%
“…Specifically, we identified increased body mass, increased RV mass, and a decreased RV ejection fraction in rats 1 year after postnatal Hx, consistent with clinical studies of adults born prematurely (10,31). Our model was also characterized by chronic RV pressure overload due to hypertensive pulmonary vascular disease, as well as intrinsic RV dysfunction noted by the inability to maintain contractility in the setting of increased afterload.…”
Section: Discussionsupporting
confidence: 83%
“…Huke 2013 and Willemsen 2008 found that preterm infants had a lower risk of central obesity than term infants in TAAT and trunk fat assessments. However, no significances were found in % IAAT and ratio of trunk fat/total fat [44,47] [48]. (Table 2).…”
Section: Plos Onementioning
confidence: 90%
“…The meta-analysis demonstrated that there was no difference in BMI between those born preterm and at term (MD, 0.13 kg/m 2 , 95% CI: −0.40 to 0.14 Supplementary Fig. 1) 16 could not be included in the meta-analysis 14,35,57,58 . Of these, one showed that obesity was more prevalent among those born preterm (Supplementary Table 1) 14 .…”
Section: Risk Factor Profile Between Those Born Preterm Compared To Termmentioning
confidence: 99%